Comparison of Student's Musical Intelligence Based On The Pianika Ensemble Extracurricular - Deavaniï¸, Ferronica Nita; Sutikno, Putri Yanuarita (Universitas Negeri Semarang, 2021)
Based on the results of pre-research observations, it is known that the musical abilities of grade V students are more developed in the realm of theoretical knowledge than the practice of playing pianica. Students understand the material of musical scales such as the concept and types of musical scales theoretically, but have difficulty applying them to the game of pianica or are less skilled at playing pianica. This study aims to determine the significant difference between the musical intelligence of students who get and do not get the pianica ensemble extracurricular. This type of research is comparative research. The sampling technique was purposive sampling. The data collection used the technique of playing pianica skills tests, interviews, observation, and documentation. The results showed that Tersobo 1 elementary school had an average score of pianica playing skills of 15.74 higher than Sidogede 2 elementary school at the pretest. In the posttest, Tersobo 1 elementary school has an average score of 13.89 higher playing pianica skills compared to Sidogede 2 elementary school. The difference in the mean value of the pretest and posttest between the two schools shows that there are differences in students' pianica playing skills. The results of hypothesis testing using the t-test independent sample t-test and obtained sig results. 0.039 The difference in the mean value of the pretest and posttest between the two schools shows that there are differences in students' pianica playing skills. The results of hypothesis testing using the t-test independent sample t-test and obtained sig results. 0.039 The difference in the mean value of the pretest and posttest between the two schools shows that there are differences in students' pianica playing skills. The results of hypothesis testing using the t-test independent sample t-test and obtained sig results. 0.0390.05. The benefit of this research was to help teachers teach pianica playing skills and to help students develop pianica playing skills. The conclusion of this study there was a significant difference between students who get and do not get the pianica ensemble extracurricular.Keywords: Musical Intelligence; piano ensemble extracurricular; piano